(3efgGL GdhUhd Edi Yde GdCUhds - (3YHO Gddg Hf YeQ Hf eMeO Hf Ydj GdTjQGRj, CHh SYjO, Ch CHh GdNjQ, fGUQ GdOjf GdHjVGhj,J (B685 (3g` s ((3eMeO Hf CMeO Hf YeQs)
(3ChdgG (B:s
(3hHYO aEfi Chdi eGJge Hg Gdgee GdYhGd hJUQa ajg GdCjGe hGddjGdi s
(3BNQgG (B:s
(3hbO GNJda ai GdCUhd hdfG ajg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B97s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1878s
Keywords: (3CUhd Gdabgs